Peran Kinerja Operasional dalam Mengelola Arus Kas Operasional PT Charoen Pokphand Indonesia Tbk - Deki Neriawan; Sri Retnaning Sampurnaningsih; Baskoro Pujo Sasmito (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the role of operational performance in managing operating cash flows at PT Charoen Pokphand Indonesia Tbk during the period 2021–2024. The research adopts a qualitative approach with a case study design. Data were collected through document analysis of annual financial statements, management reports, and an in-depth review of the company’s key operational indicators. The analysis focuses on how operational efficiency practices, production cost management, and operational policies influence the sustainability of operating cash flows. The findings indicate that operational performance plays a central role in maintaining the stability of operating cash flows, particularly through cost control, optimization of gross profit margins, and effective management of the operating cycle. Financial ratios such as the Debt to Asset Ratio, Debt to Equity Ratio, Return on Assets, and Current Ratio are used as supporting indicators to provide contextual understanding of the company’s financial condition, rather than being examined as causal relationships. These results underscore that the effectiveness of operating cash flow management is not solely determined by financial structure, but is highly dependent on the quality and consistency of operational performance. This study offers practical implications for management in formulating operational strategies oriented toward cash flow sustainability and contributes to the literature on the role of operational performance within the context of integrated agribusiness companies.